Find all such lines that are tangent to the following curves:

$$y=x^2$$ and $$y=-x^2+2x-2$$

I have been pounding my head against the wall on this. I used the derivatives and assumed that their derivatives must be equal at those tangent point but could not figure out the equations. An explanation will be appreciated.


Here is a hint for a method which avoids calculus:

The line $y=ax+b$ is a tangent to a quadratic such as $y=x^2$ if and only if the quadratic equation you get by solving these equations simultaneously has a double root. This will give you an equation which must be satisfied by the unknowns $a$ and $b$.

You can do the same for the line $y=ax+b$ and your other quadratic, then solve the two simultaneous equations to find $a$ and $b$.


If $y=x^2$ we have that $\frac {dy}{dx} = 2x$

This gives the gradient of the tangent at the point $(x, y)=(a, a^2)$

If the tangent line is $y=mx + c$ we therefore have $a^2=(2a)\cdot a+c$ whence $c=-a^2$ and the general tangent line to $y=x^2$ is $$y=2ax-a^2$$

If $y=-x^2+2x-2$ we have $\frac {dy}{dx} = -2x+2$, so that the tangent line $y=mx +c$ at $(x, y)=(b, -b^2+2b-2)$ is $-b^2+2b-2=(-2b+2)b+c$ whence $c=b^2-2$ and the general tangent to the parabola is $$y=(-2b+2)x+b^2-2$$

If the two tangents are to be the same line we equate coefficients to give:$$a=1-b$$ and $$a^2=2-b^2$$


Tangent line of first equation through some point $(x_1,f_1(x_1))$ is $$ y = f_1(x_1) + f'_1(x_1)(x-x_1) = x_1^2 + 2x_1(x-x_1) = 2x_1x-x_1^2 $$ Tangent line of second equation through some point $(x_2, f_2(x_2))$ is $$ y = f_2(x_2) + f'_2(x_2)(x-x_2) = -x_2^2+2x_2-2 + (-2x_2+2)(x-x_2) = 2(1-x_2)x+x_2^2-2 $$ In order these two lines to be the same one must require $$ 2x_1 = 2(1-x_2) \\ -x_1^2 = x_2^2-2 $$ It is quite simple to solve so I leave it to you. Solution is $$ k = 1 \pm \sqrt 3 \\ b = -1 \pm \frac {\sqrt 3}2 $$ for the line $y = kx + b$.


  • $\begingroup$ Thanks for this answer. There is something that I do not understand: If you equal both 1st and 2nd equations, you reach to the following equation: $$ 2x_1x-x_1^2 = 2(1-x_2)x+x_2^2-2 $$ which is one equation and two unknowns ($x$ and $x_2$). How do you solve it? I would appreciate very much if you could answer me please. Thanks a lot $\endgroup$ – DavidC. Oct 18 '17 at 13:12
  • $\begingroup$ @DavidC. hey, sorry for the late response. I think you misunderstood the statement, you don't have to solve the equation you wrote. Instead you need to find such values of $x_1$ and $x_2$ that make both sides the same. You do that by equating corresponding coefficients. I hope that clarifies it. $\endgroup$ – Kaster Oct 23 '17 at 17:32

enter image description here

Let $f(x) = x^2$ and $g(x) = -x^2 + 2x - 2 \implies \dfrac{d}{dx}(f(x))|_{x = a} = 2a$ and $\dfrac{d}{dx}(g(x))|_{x = b} = -2b + 2$

$2a = -2b + 2 \implies a = 1 - b \implies$

$A: (1 - b, (1 - b)^2), B: (b, -b^2 + 2b - 2) \implies m_{AB} = \dfrac{2b^2 - 4b + 3}{1 - 2b} = -2b + 2 \implies $ $2b^2 - 2b - 1 = 0 \implies b = \dfrac{1 \pm \sqrt{3}}{2}$

Using $b = \dfrac{1 + \sqrt{3}}{2} \implies $

$A: (\dfrac{1 - \sqrt{3}}{2},\dfrac{2 - \sqrt{3}}{2}), B: (\dfrac{1 + \sqrt{3}}{2},\dfrac{\sqrt{3} - 4}{2}) \implies m_{AB} = 1 - \sqrt{3} \implies $ $ \boxed{y = (1 - \sqrt{3})x + \dfrac{\sqrt{3} - 2}{2}} $

Using $b = \dfrac{1 - \sqrt{3}}{2} \implies A^{'}: (\dfrac{1 + \sqrt{3}}{2}, \dfrac{2 + \sqrt{3}}{2}), B^{'}: (\dfrac{1 - \sqrt{3}}{2}, \dfrac{-\sqrt{3} - 4}{2}) \implies$ $m_{A^{'}B^{'}} = 1 + \sqrt{3} \implies \boxed{y = (1 + \sqrt{3})x - \dfrac{\sqrt{3} + 2 }{2}}. $


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.